Pengaruh Pelayanan Islami Terhadap Kepuasan Konsumen Di 212 Mart Purwakarta - Nasih Sariningsih; Saepul Bahri; Ayi Nurbaeti (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2020)
The purpose of this research is to measure and analyze how much influence the Islamic service has on consumer satisfaction at 212 Mart Purwakarta. The sample of this research is 212 Mart Purwakarta consumers as many as 92 people. The formula for determining the sample uses the Slovin formula. Data collection was carried out by distributing questionnaires using a Likert scale to 92 respondents. The method used is a quantitative method, a method that uses numbers and then analyzed using the SPSS version 25 program. Data analysis techniques used in this study are validity, reliability, classical assumption tests include normality and linearity tests, while hypothesis testing include partial test (t), coefficient of determination analysis (r2) and simple regression analysis. The results showed that the independent variable (Islamic service) was proven to be positive and significant effect on the dependent variable (Consumer Satisfaction) of 57.7% with a significance value of 0,000 <0.05 and a regression coefficient of X of 0.281 which means that each addition of 1% value Islamic services, the value of consumer satisfaction increases by 0.281. while the remaining 42.3% by other variables outside the variables used in this study.